Clitics between syntax and lexicon - Gerlach, Birgit (Linguistik aktuell ;, 2002)
As a typical interface phenomenon, clitics have become increasingly important in linguistic theory during the last decade. The present book contributes to the recent discussion and first provides a comprehensive overview of clitic sequencing, clitic placement and clitic doubling in the major Romance languages. In addition, new data from a northern Italian dialect are introduced. The author then gives a critical summary of the current morphological analyses of clitic phenomena. She also discusses recent Optimality-theoretical analyses of clitic combinations and clitic placement and shows how th.